2020
DOI: 10.1007/s12035-020-01899-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Transcriptome Analysis Identifies FXN and BDNF as Novel Targets of miRNAs in Friedreich’s Ataxia Patients

Abstract: Friedreich's ataxia (FRDA) is a genetic neurodegenerative disease that is caused by guanine-adenine-adenine (GAA) nucleotide repeat expansions in the first intron of the frataxin (FXN) gene. Although present in the intron, this mutation leads to a substantial decrease in protein expression. Currently, no effective treatment is available for FRDA, and, in addition to FXN, other targets with therapeutic potential are continuously sought. As miRNAs can regulate the expression of a broad spectrum of genes, are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…A plausible alternative, at least for ONs targeting the 3′ UTR, would be interference with miRNAs regulating the FXN transcript. However, analysis of our comprehensive miRNA-seq data from FRDA and control fibroblasts ( 45 ) indicates that none of the miRNAs expressed in fibroblasts is likely to compete with ET3 or ET4 for binding of the FXN transcript 3′ UTR. Further studies designed to dissect mechanism(s) responsible for extension of the mRNA half-life may result in development of more efficient strategies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A plausible alternative, at least for ONs targeting the 3′ UTR, would be interference with miRNAs regulating the FXN transcript. However, analysis of our comprehensive miRNA-seq data from FRDA and control fibroblasts ( 45 ) indicates that none of the miRNAs expressed in fibroblasts is likely to compete with ET3 or ET4 for binding of the FXN transcript 3′ UTR. Further studies designed to dissect mechanism(s) responsible for extension of the mRNA half-life may result in development of more efficient strategies.…”
Section: Discussionmentioning
confidence: 96%
“…Total RNA was extracted using the RNeasy Mini Kit (Qiagen, Cat# 10074) and treated with DNase I (TURBO DNA-free; Thermo Fisher, Cat# AM1907) for 1 h according to the manufacturer’s protocol. The qRT-PCR reactions were assembled using the Power SYBR Green RNA-to-CT 1-Step Kit (Thermo Fisher, Cat# 4391178) and run on a Step-One Plus System (Applied Biosystems) as we described in ( 41 , 45 ). Reverse transcription was conducted at 48°C for 30 min, followed by 40 cycles of denaturation at 95°C for 15 s, annealing at 55°C for 20 s and elongation for 1 min at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the SCA6 pathogenic mechanism is associated with the abnormal localization of BDNF proteins and a reduction in BDNF mRNA expression. A comprehensive transcriptome analysis in Friedreich’s ataxia (FRDA) patients, a hereditary neurodegenerative disease characterized by guanine-adenine-adenine (GAA) nucleotide repeat expansion in the first intron of the frataxin (FXN) gene, identified BDNF and FXN as novel targets of miRNAs [ 137 ].…”
Section: Bdnf In Other Neurodegenerative Diseasesmentioning
confidence: 99%
“…Furthermore, BDNF is secreted, which implies that not only the transduced cells will increase their BDNF levels, but also the neighboring cells. Moreover, it was recently demonstrated that an miRNA targeting BDNF is increased in fibroblasts from FA patients and that, coherently, BDNF levels are reduced [ 98 ]. Therefore, BDNF is a potential candidate for the treatment of neurodegenerative diseases, and especially for FA.…”
Section: Gene Therapy In Friedreich’s Ataxiamentioning
confidence: 99%